Shariah objectives and their effects on contracts - Alsbeinaty, Ridwan Eyup (Journal of Economic, Administrative and Legal Sciences, 2022)
This study used a deductive approach to determine the Sharia objectives in ruling some contracts to be forbidden, an analytical approach to determine the aims of competent individuals, an inductive approach to determine the views of jurisprudents regarding Murabaha contracts, and a comparative approach to compare the objectives of Sharia to the contractor’s aims and goals in their contracts. The study provides some recommendations including the need for an increased focus on the study of Sharia objectives and to adopt this branch of study as a set of standards to promote the jurisprudential view and control similar issues; and the need to achieve an Islamic banking model that achieves the Sharia objectives and provides opportunities for societal development The study developed a mechanism for an aims- oriented view to deal with suspicions arising around contracts, within a methodology that enables jurisprudential preference according to the Sharia objectives, in order to reach Sharia rulings that align and agree with Sharia objectives.